2018
DOI: 10.1007/s12035-018-1174-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance 1 Modulates Glycolytic Pathways in the Cerebellum via an Interaction with Glucose-6-Phosphate Isomerase

Abstract: Glucose metabolism is essential for the brain: it not only provides the required energy for cellular function and communication but also participates in balancing the levels of oxidative stress in neurons. Defects in glucose metabolism have been described in neurodegenerative disease; however, it remains unclear how this fundamental process contributes to neuronal cell death in these disorders. Here, we investigated the molecular mechanisms driving the selective neurodegeneration in an ataxic mouse model lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…It has been shown recently that Oxr1 regulates the activity and degree of oligomerization of the multifunctional enzyme glucose-6-phosphate isomerase (GPI/Gpi1) via protein-protein interaction [27]. Therefore, seeing that Oxr1 can influence ROS levels as well as protein multimer formation and aggregation, we tested the hypothesis that Oxr1 is neuroprotective against O/N stress by regulating the function of essential proteins within these two pathways [26,28,36,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown recently that Oxr1 regulates the activity and degree of oligomerization of the multifunctional enzyme glucose-6-phosphate isomerase (GPI/Gpi1) via protein-protein interaction [27]. Therefore, seeing that Oxr1 can influence ROS levels as well as protein multimer formation and aggregation, we tested the hypothesis that Oxr1 is neuroprotective against O/N stress by regulating the function of essential proteins within these two pathways [26,28,36,41].…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive Oxr1 knockout ( Oxr1 d/d ) mice maintained on a C57BL6/J background have been previously described [27]. Oxr1 Tg mice, where a full-length cDNA transgene of Oxr1-FL is expressed from a ubiquitous actin-derived promoter, were also maintained on a C57BL6/J background and have been previously described [28].…”
Section: Methodsmentioning
confidence: 99%
“…We also explored a relatively novel protein, oxidation resistance 1 (Oxr1), that has been implicated as necessary for oxidative stress protection, perhaps especially in neuronal cells. Originally identified in bacteria to protect against oxidative DNA damage [63], it has been shown to protect against neurodegeneration in mammals [64,65], potentially through its partnership with peroxiredoxin 2 [66]. Multiple isoforms of Oxr1 are found in mammalian cells, with the high molecular weight forms (55kD and greater) primarily located in the cytoplasm, whereas the smaller isoforms (less than 55kD) localize to mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we recently demonstrated that Oxr1 modulates the activity of glucose-6-phosphate isomerase (Gpi1) and peroxiredoxin 2 (Prdx2), which can be secreted by neurons to activate glial cells and thus contribute to the inflammatory response. (55,58–60). Another possibility would be that Oxr1 over-expression leads to a global reduction of ROS levels within neurons, leading to a reduction in proinflammatory signals released by neurons, which is often associated with sustained oxidative stress conditions and an inhibition of inflammation in the central nervous system (61).…”
Section: Discussionmentioning
confidence: 99%